Descriptive Analysis of Financial Literacy: Evidence from Public and Private University Students - Budi Setiawan (Faculty of Economics, Universitas Sriwijaya, 2020)
Financial knowledge plays a pivotal role to survive in modern society. The study measures the financial literacy level of public and private university students in Palembang, Indonesia by distributing an online questionnaire to 608 respondents. The questions of financial literacy refer to the Standard & Poor’s Rating Services, which covered three subjects, namely numeracy and compound interest, inflation, and risk diversification. For this purpose, the level of financial literacy was conducted using descriptive statistics (Eviews). The result shows that there is 12% of the respondents from public universities answered all questions correctly, which is relatively high compared to private university students are at 10%. In addition, more than half of respondents are able to answer the question about numeracy and compound interest correctly, and inflation is 39%. On the other hand, the score is only 27% for the correct answer related to risk diversification. Financial illiteracy consequences are poor financial decisions that can impact their future finance.